Tipologi Permukiman Kumuh di Kelurahan Kapuk, Jakarta Barat - Maharani, Alexandra Valencia; Aditantri, Rahmatyas (LPPM Universitas Terbuka, 2025)
This study analyzes the slum level in Kapuk Subdistrict, West Jakarta, using indicators from the Ministry of Public Works Regulation No. 14 of 2018. Kapuk faces challenges such as high population density, inadequate infrastructure, and limited access to basic facilities. Data collection methods included field observations, questionnaires, interviews, and literature studies. Slum scores were calculated based on indicators such as building conditions, roads, drinking water, drainage, waste management, and fire protection. The results show that most areas are categorized as mildly slum, with only one area (RW 07) classified as moderately slum. Major issues include narrow roads, poor drainage, and limited access to clean water. This study recommends infrastructure interventions, sanitation improvements, and enhanced social facilities to prevent further slum deterioration. These findings aim to guide priorities for slum settlement management planning.